2021
DOI: 10.1186/s13063-021-05166-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of opioid-free anesthesia on the quality of recovery after gynecological laparoscopy: study protocol for a prospective randomized controlled trial

Abstract: Background Because of the indiscriminate use of opioids during the perioperative period, opioid-free anesthesia (OFA) has been increasingly required. Nevertheless, the studies on the detailed techniques and effects of OFA are not sufficient. The Quality of Recovery-40 (QoR-40) questionnaire is a validated assessment tool for measuring recovery from general anesthesia. However, no study has used the QoR-40 to determine if OFA leads to better recovery than standard general anesthesia. Therefore, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“… 12 In terms of physical discomfort and physical independence, the current results are consistent with the findings from a recent study, which revealed that the incidence of PONV in Group OA after gynecological surgery was higher than in Group OFA. 13 Combined with our results, we speculate that intraoperative opioid use might increase the risk of PONV and may result in poor sleep quality and worse diet quality. Esketamine is a valid analgesic alternative to opioids to avoid opioid-related nausea and vomiting in the postoperative setting.…”
Section: Discussionsupporting
confidence: 74%
“… 12 In terms of physical discomfort and physical independence, the current results are consistent with the findings from a recent study, which revealed that the incidence of PONV in Group OA after gynecological surgery was higher than in Group OFA. 13 Combined with our results, we speculate that intraoperative opioid use might increase the risk of PONV and may result in poor sleep quality and worse diet quality. Esketamine is a valid analgesic alternative to opioids to avoid opioid-related nausea and vomiting in the postoperative setting.…”
Section: Discussionsupporting
confidence: 74%
“…Full details of the study protocol have been published previously. 18 Written informed consent was obtained from all participating patients before inclusion in the study. The study is reported according to the Consolidated Standards of Reporting Trials (CONSORT) 2010 Statement and the CONSORT Patient-Reported Outcomes (CONSORT PRO) Extension.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the Ramsay scores in the experimental group were significantly higher than those in the observation group after treatment, indicating that dexmedetomidine provides more sedative benefits in patients undergoing laparoscopic gynecological surgery. Song et al, [21] indicated that 0.6 µg/kg of dexmedetomidine administered 30 min before induction of anesthesia could effectively ensure the intraoperative hemodynamic stability of patients and well inhibit the extubation reflex.…”
Section: Resultsmentioning
confidence: 99%